Analyzing the Market Concentration of the Romanian Capital Market - Cioacă Sorin-Iulian (Hyperion Economic Journal, 2015)
The market concentration is an important issue for the competition and supervision authorities, as they are entitled to find the proper measures assuring the stability and fair competition of the markets. In this article, we analyze the market concentration of the Romanian capital market, using the market share of every intermediary, for the 2007-2014 time period. We compute the concentration ratios for the first 4 and 8 largest intermediaries, finding that the Romanian capital market is not concentrated. But the recent trends show early phases of concentration, as the number of brokerage houses decline and the trading activity become concentrated in the first 8 brokerage houses.